The Influence of Work Facilities on Job Satisfaction and Employee Performance in the Hospital Administrative Unit - Julyanthry Julyanthry; Adrian K Tarigan; Sabar Dumayanti Sihombing; Injen Pardamean Butarbutar; Richard Berlien (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Employee performance is crucial for hospital service quality, yet limited work facilities remain a barrier to satisfaction and productivity. This study aims to analyze the influence of workplace facilities on job satisfaction and employee performance in the administrative unit. The research used a combination of field research and library research methods. The population consisted of all 33 administrative staff members. Data analysis techniques included normality tests, qualitative descriptive analysis, and multiple linear regression. The results showed that workplace facilities were rated as good. Employees reported a satisfactory level of job satisfaction, although aspects such as work challenges and reward systems need improvement. Employee performance was also rated as good, especially in terms of discipline and punctuality, while initiative was hindered by monotonous work routines. Quantitative analysis revealed a moderately strong correlation between workplace facilities and both job satisfaction and employee performance. Workplace facilities accounted for 56.3% of the variance in job satisfaction and 48.5% in employee performance. Regression analysis confirmed that workplace facilities have a statistically significant effect on both job satisfaction and performance. These findings highlight the critical role of workplace facilities in enhancing human resource quality within hospital administrative environments.